Identification and Biological Evaluation of Secondary Metabolites from the Endolichenic Fungus Aspergillus versicolor - Li, Xiao-Bin; Zhou, Yan-Hui; Zhu, Rong-Xiu; Chang, Wen-Qiang; Yuan, Hui-Qing; Gao, Wei; Zhang, Lu-Lu; Zhao, Zun-Tian; Lou, Hong-Xiang (Chemistry & biodiversity, 2015)
A chemical investigation of the endolichenic fungus Aspergillus versicolor (125a), which was found in the lichen Lobaria quercizans, resulted in the isolation of four novel diphenyl ethers, named diorcinols F–H (1–3, resp.) and 3‐methoxyviolaceol‐II (4), eight new bisabolane sesquiterpenoids, named (−)‐(R)‐cyclo‐hydroxysydonic acid (5), (−)‐(7S,8R)‐8‐hydroxysydowic acid (6), (−)‐(7R,10S)‐10‐hydroxysydowic acid (7), (−)‐(7R,10R)‐iso‐10‐hydroxysydowic acid (8), (−)‐12‐acetoxy‐1‐deoxysydonic acid (9), (−)‐12‐acetoxysydonic acid (10), (−)‐12‐hydroxysydonic acid (11), and (−)‐(R)‐11‐dehydrosydonic acid (12), two new tris(pyrogallol ethers), named sydowiols D (13) and E (14), and fifteen known compounds, 15–29. All of the structures were determined by spectroscopic analyses, and a number of them were further identified through chemical transformations and electronic circular dichroism (ECD) calculations. Preliminary bioassays of these isolates for the determination of their inhibitory activities against the fungus Candida albicans, and their cytotoxicities against the human cancer cell lines PC3, A549, A2780, MDA‐MB‐231, and HEPG2 were also evaluated.